Implementasi Penilaian Sikap pada Pelajaran Pendidikan Agama Islam Materi Sholat Fardhu untuk Meningkatkan Iman Kepada Allah Swt Kelas V di sekolah Dasar - Shalwa Fauziyah Leksono; Adinda Putri Ramadhani; Enung Nugraha (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to determine the benefits of assessing attitudes (affective) in Islamic religious education (PAI) lessons in elementary schools. This research uses a qualitative method which aims to gain a deeper understanding of the use of attitude (affective) assessment in Islamic religious education (PAI) lessons in elementary schools. So, the data collection method used uses previous research data, then the data is analyzed using data obtained from relevant sources. After previous research has been analyzed, the conclusion of this research is that although behavioral assessment requires students to behave in accordance with Islamic values, their behavior often does not go well. Teachers tend to focus on skills assessment and face difficulties in creating clear and consistent assessment tools. To overcome this problem, more efforts need to be made to assess the importance of assessment by using assessment and testing tools. Additionally, behavioral assessments should be included in the report card and not just as a formality. In this way, it is hoped that the PAI learning process can be more meaningful and contribute to the formation of students' character as a whole.